A TWO-PHASE SOLUTION APPROACH FOR A MANUFACTURING-DISTRIBUTION PROBLEM WITH REWORK, OUTSOURCING, AND MULTI-SHIPMENT POLICY - Chiu, Yuan-Shyi Peter; Sung, Peng-Cheng; Chiu, Victoria (Journal of Applied Engineering Science, 2020)
A manufacturing batch-size and end-product shipment problem with outsourcing, multi- shipment, and rework was investigated in a recent article [1] using the mathematical modeling and derivatives in their solution procedure. The present work employs an alternative method namely, a two-phase algebraic approach to resolve the problem in [1] and determine the optimal manufacturing batch-size and end-product shipment policies that keep total system cost at minimum. Such a straightforward solution process enables the practitioners in production planning and controlling filed, who may have inadequate knowledge of the differential calculus, to comprehend and easily solve the best replenishing batch-size and shipment policies of this realistic problem.